Pectinmethylesterase from the rice weevil, Sitophilus oryzae: cDNA isolation and sequencing, genetic origin, and expression of the recombinant enzyme - Shen, Zhicheng; Pappan, Kirk; Mutti, Navdeep S.; He, Qi-Jiong; Denton, Michael; Zhang, Yu; Kanost, Michael R.; Reese, John C.; Reeck, Gerald R. (My University, 2008)
A cDNA clone encoding pectinmethylesterase of the rice weevil, Sitophilus oryzae (L.) has been isolated and sequenced. The cDNA clone was expressed in cultured insect cells and active pectinmethylesterase was purified from the culture medium, thus confirming that the cDNA encodes pectinmethylesterase. In situ hybridization indicated that the enzyme's transcript was present in the midgut. Weevils treated with tetracycline so that they lack genes of known symbiotic organisms still contained the pectinmethylesterase gene, indicating that the gene is encoded by the rice weevil genome. The rice weevil enzyme is most similar in sequence to bacterial pectinmethylesterases. Given this and the enzyme's apparently rather general absence from animal species, we suggest the possibility that this gene was transferred horizontally to an ancient weevil, possibly from a bacterial symbiont, and exists in Sitophilus species now as a result of that ancestral horizontal transfer.
Citation: Shen Z, Pappan K, Mutti NS, He Q-J, Denton M, Zhang Y, Kanost MR, Reese JC, & Reeck, GR. (2005). Journal of Insect Science, 5(21), 1-9. https://doi.org/10.1673/031.005.2101
Keywords: Pectinase; Pectin esterase; Polygalacturonase; Gut; Digestive enzyme; Pectin; Symbiont; Wolbachia; SOPE; Gene transfer